Effects of manual, chemical and enzymatic peeling methods on physicochemical and microbiological properties of Malaysian Mango (Mangifera indica L. Cv. `Chok Anan') puree - Mohamad, Nur Sadrina (2016)
Mango is an intermediate product applied to several products as juices, nectars and purees but it requires peeling before further processing. Conventional peeling has been implemented, but it is time-consuming and requires laborious work. Therefore, this study aimed to determine the optimum conditions of selected peeling methods (chemical and enzymatic) of Malaysian „Chok Anan‟ mango fruit on physicochemical properties, polyphenol oxidase (PPO), respiration rate and microbiological analysis of mango puree. Optimization of peeling conditions was carried out using the Response Surface Methodology (RSM) to study the effect of chemical (sodium hydroxide, NaOH) and enzyme (Pectinex Ultra SP-L) based on concentrations (chemical: 1.6-7.3 g/100mL; enzyme: 0.005-0.095% (v/v)), temperatures (chemical: 80-95 ; enzyme: 25-40 ) and soaking durations (chemical: 5-10 min; enzyme: 30-120 min) on the mango fruit. Peeling yield and the effect of the different peeling methods on moisture content (%), color changes and viscosity (Pa.s) of mango puree were investigated. The optimum concentration of 7.3 g/100mL; temperature at 95 and duration of 8.5 min for soaking were selected for chemical peeling. The optimized concentration and temperature of NaOH applied in this study were the most significant factors (p<0.05) affecting the peeling yield (88.72%), moisture content (86.19%), color ( dE = 62.00) and viscosity (0.2169 Pa.s) of mango puree. The optimum conditions for enzymatic peeling (pectinase solution) were at concentration of 0.009%; temperature, 25 , and duration of soaking for 120 min. The pectinase concentration, temperature and duration of soaking had significantly (p<0.05) affected the quality of the Malaysian „Chok Anan‟ mango puree with enhanced yellow color ( dE = 67.02), low viscosity (0.1739 Pa.s) and low moisture content (82.67%). Enzymatic peeling significantly (p<0.05) reduced the peeling time (4.46 min) of mango puree production compared to both manual (5.30 min) and chemical (6.49 min) peeling. In addition, absorption of chemical (0.84 g/100g) and enzyme (2.50 g/100g) solutions, penetration depth of NaOH (0.45 mm), enzyme activity (0.48-0.63 g/100mL) were analysed for the peeling efficiency of chemical and enzymatic peeling methods. Based on the results, enzymatically peeled mango puree had significantly (p<0.05) the lowest moisture content (84.04-84.44%), lowest pH (4.54 – 4.67), acidic (TA = 0.08-0.10%), yellower in color ( dE = 61.72), highest total soluble solids (TSS) content (16.0-16.9 oBrix), highest vitamin C content (1.80 mg/100g) compared to manual-peeled (moisture content = 84.73-86.39%, pH = 4.51-4.88, TA = 0.09-0.14%, dE = 61.00, TSS = 15.0-16.0 oBrix, vitamin C = 1.42 mg/100g) and chemical-peeled (moisture content = 84.43-88.23%, pH = 5.20–5.36, TA = 0.06-0.07%, dE = 59.80, TSS = 15.0-15.7 oBrix, vitamin C = 1.42 mg/100g) mango puree. There was significantly (p<0.05) decreased (manual: 20.4-20.2 kPa, chemical: 20.3-20.0 kPa, enzymatic: 20.7-19.5 kPa) in oxygen composition and increased of carbon dioxide (manual: 0.64-0.80 kPa, chemical: 0.46-3.03 kPa, enzymatic: 0.64-2.60 kPa) reflected a high respiration rate occurred over storage period. Furthermore, enzymatic-peeled mango puree stored at 4±2 had significantly (p<0.05) the lowest total plate counts (6.8 log CFU/g) compared to the manual-peeled (7.8 log CFU/g) mango purees at the end of 26 days of storage. Yeast and mold counts of enzymatically peeled mango puree shows significantly (p<0.05) the lowest count (6.5 log CFU/g) compared to manual-peeled (7.8 log CFU/g) and chemical-peeled (8.3 log CFU/g) after 26 days of storage. Storage of mango puree at 4±2 shows significantly longer shelf life (26 days) compared to 20±2 (ambient temperature) for only 3 days. This study suggested that enzymatic peeling can be an alternative peeling method other than manual peeling and effective with the recyclability of the pectinase used throughout the mango processing. The development of effective peeling method may be useful to assist the puree production of mango industries.